Seismic fragility estimates of a moment-resisting frame building controlled by MR dampers using performance-based design. (1st June 2016) - Cha, Young-Jin; Bai, Jong-Wha
Highlights: Fragility analyses were carried out for the controlled structures using large-scale MR dampers. System reliability approach is adopted and the results are compared to the traditional approach. The seismic fragilities are quite reduced by application of the MR dampers. The vulnerability with lower target interstory drift is quite less than those with higher target. The DPBD method provides significantly improved seismic performances. Abstract: Seismic fragility was estimated for a controlled high-rise building using 200 kN magnetorheological (MR) dampers with direct performance-based design (DPBD) to assess seismic vulnerability and to validate the performance of the DPBD which was previously developed. The DPBD offers multiple control design layouts for various performance levels subjected to different hazard levels using multi-objective optimization approaches. These multiple control design layouts for the given performance levels need to be validated using random seismic excitations because those performance-based designs (PBD) had been devolved based on the specific strength of design objective earthquakes (i.e., hazard levels) from the DPBD. In order to evaluate those PBD cases using MR dampers, two different approaches for fragility estimation of the four PBD cases under two hazard levels are conducted: traditional approach using the overall maximum interstory drift and system reliability approach which considers multiple limit states associated with the maximum interstory drift for stories within the entire system. The results are compared using 41 earthquake ground motions. From this study, overall seismic fragility relations have been derived from extensive fragility analyses in terms of broad range of hazard levels for multiple performance levels which were achieved by new direct performance-based design using MR dampers. Moreover, it is observed that the multiple performance-based control design cases obtained from DPBD clearly show significant reduction in seismic vulnerability compared to the uncontrolled case. It also shows different seismic fragility estimates against seismic hazards reflecting the performance enhancement based on the initial objective of the DPBD. Based on the results, the system reliability approach can identify the stories that have close interstory drifts to the overall maximum value allowing for more accurate estimates of the seismic fragility of multi-story buildings.